Construction of hybrid autonomous and backup power supply for complex solar systems - Єрохов, Валерій Юрійович; Дружинін, Анатолій Олександрович; Єрохова, Ольга Валерієвна (Technology audit and production reserves, 2015)
The perspective hybrid autonomous and reserve power supply system, which is used in a complex heliosystems was developed by using of renewable energy sources in the form of photovoltaic panels, rechargeable batteries, charge controller and inverter, that converts the low-voltage constant current 12-24 V to the consumer standard ~ 220 V. This hybrid system was used in a complex heliosystems (in the case of unstable lighting – the solar panels on the roof and walls simultaneously are disposed or on the East - West are disposed etc.). Optimization (replacement) of the solar controller is the first step to the power generation increase by solar batteries, without solar panels adding. The most effective model of microcontroller unit for construction of a hybrid autonomous and emergency power supply system was investigated and developed by using of a Pulse-Width Modulation (PWM), as well as the solar battery Maximum Power Point Tracking (MPPT), which are used in a complex heliosystems maximum performance set up. This paper also consider the possibility to use of “intelectual” microcontrollers as control elements of microcontroller block to build an effective model of hybrid power supply system microcontroller unit for it maximum productivity setup. Microcontrollers with the MPPT technology of maximum power point tracking show a considerable advantages over other types of microcontroller block, such as low power microcontroller MPT612 with 32-bit RISC-processor ARM7TDMI-S.